Microbial Community Pathways for the Production of Volatile Fatty Acids From CO2 and Electricity - Wenzel, Jorge; Fiset, Erika; Batlle-Vilanova, Pau; Cabezas, Angela; Etchebehere, Claudia; Balaguer, María D.; Colprim, Jesús; Puig, Sebastià (Frontiers in Energy Research, 2018)
This study aims at elucidating the metabolic pathways involved in the production of volatile fatty acids from CO2 and electricity. Two bioelectrochemical systems (BES) were fed with pure CO2 (cells A and B). The cathode potential was first poised at −574 mV vs. standard hydrogen electrode (SHE) and then at −756 mV vs. SHE in order to ensure the required reducing power. Despite applying similar operation conditions to both BES, they responded differently. A mixture of organic compounds (1.87 mM acetic acid, 2.30 mM formic acid, 0.43 mM propionic acid, 0.15 mM butyric acid, 0.55 mM valeric acid, and 0.62 mM ethanol) was produced in cell A while mainly 1.82 mM acetic acid and 0.23 mM propionic acid were produced in cell B. The microbial community analysis performed by 16S rRNA gene pyrosequencing showed a predominance of Clostridium sp. and Serratia sp. in cell A whereas Burkholderia sp. and Xanthobacter sp. predominated in cell B. The coexistence of three metabolic pathways involved in carbon fixation was predicted. Calvin cycle was predicted in both cells during the whole experiment while Wood-Ljungdahl and Arnon-Buchanan pathways predominated in the period with higher coulombic efficiency. Metabolic pathways which transform organic acids into anabolic intermediaries were also predicted, indicating the occurrence of complex trophic interactions. These results further complicate the understanding of these mixed culture microbial processes but also expand the expectation of compounds that could potentially be produced with this technology.